The Influence of Corporate Governance, Gender Diversity, CSR on Tax Aggressiveness in Companies Listed on the IDX - Nurhana Hana; Riana Dewi; Anita Wijayanti (Politeknik Negeri Madiun, 2022)
For companies with a high tax burden, the company's profit will decrease. The company will take tax-saving measures, so that the tax paid is small while the profit earned is large. The higher the company's tax savings, the more aggressive the company is towards taxes. The purpose of this study is to examine and analyze the effect of corporate governance (independent commissioners, audit committees, institutional ownership), gender diversity on the board, and corporate social responsibility to tax aggressiveness. The sampling in this study using purposive sampling. The sample companies ini this study amounted to 11 companies that had met the sampling criteria. The data analysis technique used in this research is multiple linear analysis. The results showed that the independent commissioner variables and gender diversity on the board had an effect on tax aggressiveness. Meanwhile, the audit committee, institutional ownership, and corporate social responsibility (CSR) have no effect on tax aggressiveness.